Origin of arsenic and other heavy metals in the rivers of Nepal - Emerman, Steven H.; Bhattarai, Tara N.; Adhikari, Danda P.; Joshi, Sunendra R.; Lakhe, Siddhi L.; Luhrs, Aimee J.; Prasai, Kangada R.; Robson, Kristine L. (Journal of Nepal Geological Society, 2019)
The objective of this study was to determine which geological zones are contributing As and other heavy metals to the rivers of Nepal. The objective was carried out by measuring concentrations of As, Fe, Co, Cu, and Zn in rivers dissecting highgrade metamorphic Higher Himalayan rocks of the Khumbu region and comparing them with previously collected data from other geological zones. Concentrations were measured using portable colorimeters and the Hach As test kit in 153 samples collected from 108 locations over two years. For the Khumbu region, <1% of samples had As concentrations meeting or exceeding the WHO standard of 10 mcg/l, while 53% of samples from other geological zones had As ³10 mg/l. This result is consistent with the typical low As concentration of schists and gneisses. The elevated levels of fluvial As are not predicted by any of the proposed mechanisms for release of As into groundwater in the Terai region. This suggests that the kinetics of the proposed mechanisms is too slow and, at least in terms of As, the groundwater chemistry is a rough reflection of the surface water chemistry. The suggestion could be tested by measuring groundwater Co, Ni, and Cu in the Terai since almost all rivers in Nepal have elevated levels of those heavy metals. Rivers in the Khumbu region that are fed by glacial meltwater have significantly more Fe and Co than rivers fed by springs or snowmelt, suggesting that unmapped deposits of Fe and Co exist in the Tibetan-Tethyan Zone.